2009
DOI: 10.1128/aac.01175-08
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Properties of Ellagic Acid in Malaria Treatment

Abstract: Malaria is one of the most significant causes of infectious disease in the world. The search for new antimalarial chemotherapies has become increasingly urgent due to the parasites' resistance to current drugs. Ellagic acid is a polyphenol found in various plant products. In this study, antimalarial properties of ellagic acid were explored. The results obtained have shown high activity in vitro against all Plasmodium falciparum strains whatever their levels of chloroquine and mefloquine resistance (50% inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
145
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(151 citation statements)
references
References 27 publications
5
145
0
1
Order By: Relevance
“…15 From a mechanistic point of view, several studies suggest that ellagic acid (1) inhibits important enzymes necessary for the development of Plasmodium, such as plasmepsin II, β-hematin or glutathione-S-transferase. 45,49 Studies have shown that the inhibitory effect of ellagic acid on plasmepsin II was not the main mechanism. It is suggested that the inhibition of β-hematin formation should be conditioned by the ability of ellagic acid to form a π-π complex, increasing its affinity for hematin monomers.…”
Section: Biological Studymentioning
confidence: 99%
See 4 more Smart Citations
“…15 From a mechanistic point of view, several studies suggest that ellagic acid (1) inhibits important enzymes necessary for the development of Plasmodium, such as plasmepsin II, β-hematin or glutathione-S-transferase. 45,49 Studies have shown that the inhibitory effect of ellagic acid on plasmepsin II was not the main mechanism. It is suggested that the inhibition of β-hematin formation should be conditioned by the ability of ellagic acid to form a π-π complex, increasing its affinity for hematin monomers.…”
Section: Biological Studymentioning
confidence: 99%
“…According to the literature, ellagic acid was tested in several cell lines to evaluate its cytotoxic potential such as primarily MRC5 (human diploid embryonic lung), KB (human epidermoid carcinoma) and Vero (African green monkey kidney), and had no cytotoxicity at 100 µM concentration. 45 Usually cytotoxicity assays for the screening of antimalarial agents employ cell lineages from liver, blood, kidney, skin and nerve cells. 48 In order to evaluate the cytotoxic potential of ellagic acid in normal cells, it was tested in mouse peritoneal macrophages, presenting CC 50 = 9.0 ± 0.1 µg mL -1 and selectivity index (SI) = 414.7.…”
Section: Biological Studymentioning
confidence: 99%
See 3 more Smart Citations